Pengaruh Kualitas Pelayanan dan Brand Image terhadap Minat Beli Ulang dengan Kepuasan Pelanggan sebagai Variabel Mediasi Pada Restoran The Little Korean Kitchen di Munggu, Badung - Parsini, Ni Made; Putu Widani Sugianingrat, Ida Ayu; Pratiwi, Komang Ary (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
The aim of this research is to determine the influence of customer satisfaction in mediating the relationship between the influence of service quality and brand image on repurchase intention. This research was conducted by The Little Korean Kitchen Restaurant with a sample size of 96 people using the purposive sampling method. The results of the respondents' answers were continued with validity and reliability tests, then continued with hypothesis testing using path analysis and Sobel test. The results of the analysis show that 1) service quality has a positive and significant effect on repurchase interest, 2) brand image has a positive and significant effect on repurchase interest, 3) service quality has a positive and significant effect on customer satisfaction, 4) brand image has a positive and significant effect on customer satisfaction, 5) customer satisfaction has a positive and significant effect on repurchase interest, 6) customer satisfaction plays a positive and significant role in mediating service quality on repurchase interest, 7) customer satisfaction plays a positive and significant role in mediating brand image on repurchase interest.